Determinants of Priority Conflict on City School Boards. (December 2021) - Ford, Michael R.; Ihrke, Douglas M.
In this article, the authors use original survey data to test the determinants of priority conflict on urban school boards in the United States. The results indicate that school district demographics, including the percentage of English language learners and education spending per pupil, impact the extent to which urban school board members hold conflicting priorities. In addition, boards whose members indicate they engage in continuous strategic planning exhibit comparably lower levels of priority conflict. The results are of interest to scholars studying the nexus of urban governing boards and performance, as well as practitioners serving on urban governing boards.